Low frequency variability of atmospheric circulation over Europe between 1785 and 1994 - Schmutz, Christoph; Wanner, Heinz (ERDKUNDE, 1998)
A decadal analysis of monthly sea level pressure fields over Europe and the adjacent North Atlantic with a correlation-based classification scheme results in 12 classes. These classes show a high variability in the frequencies of their occurrence and also in the combination between the different classes. The range of the frequency changes from one decade to another can differ up to a factor 2. The class 1 high index situation with high positive values of the North Atlantic Oscillation Index (NAOI) with a westerly flow into the continent shows an increasing frequency in the last decades, which is unique in the analyzed period of 210 years. The combinations between the different classes are not the same over the whole period of the 210 years and show differences between the 19th century and the middle of the 20th century: especially in winter, spring and autumn. In summer the most remarkable deviations are found in the Greenland Sea. While the Azores high is present very regularly, the Icelandic low almost disappears for some periods or is at least very weak. From a more theoretical point of view these changes could go together with a weakening of the thermohaline circulation. The used data set NDP-025 (Numeric Data Package) from CDIAC (Carbon Dioxide Information Analysis Center) shows statistical significant smaller variances for the reconstructed period than in the measured period especially in the border areas of the perimeter. The classes have typical temperature means for three stations in Switzerland (Basel, Geneva and Grand Saint Bernard) which differ from each other significantly. Winter temperature with an eastern European anticyclone together with a high index situation are lower compared to a similar pressure situation without the Russian anticyclone. This specific case shows that the NAOI is not very meaningful for Central and Eastern Europe. In some cases the continental signal is almost independent of the NAOI. Depending on the frequency and temperature anomalies of the different classes, these can be subdivided into two groups with high or low climate relevance concerning the temperatures. Indifferent classes have temperatures near the seasonal mean or low frequencies. Their absence has no remarkable effect on the climate. The climate of a period therefore depends on the occurrence of classes with a high climate relevance.